2023
DOI: 10.3390/w15162994
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Runoff Estimation for Ungauged Watersheds Using a New Multisite Multivariate Stochastic Model MASVC

Joel Hernández-Bedolla,
Liliana García-Romero,
Chrystopher Daly Franco-Navarro
et al.

Abstract: Precipitation is influential in determining runoff at different scales of analysis, whether in minutes, hours, or days. This paper proposes the use of a multisite multivariate model of precipitation at a daily scale. Stochastic models allow the generation of maximum precipitation and its association with different return periods. The modeling is carried out in three phases. The first is the estimation of precipitation occurrence by using a two-state multivariate Markov model to calculate the non-rainfall perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…These studies have examined how variations in surface runoff affect soil erosion and how surface runoff [39,40] soil nutrients, rainfall, land use, and land cover distribution are affected [41,42]. The SCS-CN runoff model is somewhat influenced by rainfall intensity and spatial scale [43], and this model has also been studied for the urban and watershed levels. For example, [44] discovered that in a study of impermeable surfaces and surface runoff in Xuzhou City, the reaction of urban surface runoff is more evident when the intensity of rainfall is low.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have examined how variations in surface runoff affect soil erosion and how surface runoff [39,40] soil nutrients, rainfall, land use, and land cover distribution are affected [41,42]. The SCS-CN runoff model is somewhat influenced by rainfall intensity and spatial scale [43], and this model has also been studied for the urban and watershed levels. For example, [44] discovered that in a study of impermeable surfaces and surface runoff in Xuzhou City, the reaction of urban surface runoff is more evident when the intensity of rainfall is low.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have carried out research on surface runoff, including the impact of surface runoff changes on soil erosion and the impact of rainfall, land use, and land cover distribution on surface runoff, soil nutrients [25,26], rainfall, land use, and land cover [27][28][29]. Rainfall intensity and spatial scale have a certain influence on the SCS-CN runoff model [30], and the SCS-CN runoff model has been studied at the urban and watershed levels. For example, Liu et al [31] found that the response of urban surface runoff is more obvious when the rainfall is low in a study of impervious surface and surface runoff in Xuzhou City.…”
Section: Introductionmentioning
confidence: 99%